Study to assess diabetic foot care awareness in a selected community - Narayana, Someshwara Rao Pallela (International Surgery Journal, 2020)
Background: As burden of diabetes is increasing in India, so are the foot problems associated with it. Diabetic foot conditions leading to amputation are just tip of the iceberg. Patients do not present early with the complaints, hence resulting in complications. Awareness of foot care is essential in diabetes management. This prompted us to know how much is the foot care awareness among diabetic patients. Methods: This cross-sectional study was done in 120 diabetic patients selected by purposive non probability sampling method from OPD in a teaching hospital. All the patients were given a pretested questionnaire related to foot care. Total 10 questions were given each scoring one point. Patients scoring above 5 were considered good score and less than 5 were considered poor score. History of foot ulcers and present foot ailments was also taken along with these for correlation with awareness. Data was analysed by descriptive and inferential statistics. Results: Among the 120 patients, 92 (76.6%) had good knowledge and 28 (23.3%) had poor knowledge of foot care. Among the 92 patients who had good knowledge, 35 (38%) followed foot care precautions, 57 (61.9%) did not follow. Of the 57 patients 8 (14%) had foot ulcers presently. Among 28 patients with poor knowledge of foot care, 10 (35.7%) had present history of foot ulcers. Conclusions: Education in diabetic foot care and insisting on practising them on daily basis is essential to lower the incidence of grave diabetic foot conditions which may result in amputation. Prevention of foot problems by self-precautions in patients would definitely lower the complications and the financial burden.